2016
DOI: 10.9745/ghsp-d-15-00393
|View full text |Cite
|
Sign up to set email alerts
|

Family Planning Counseling in Your Pocket: A Mobile Job Aid for Community Health Workers in Tanzania

Abstract: Using mobile job aids can help CHWs deliver integrated counseling on family planning and HIV/STI screening by following a step-by-step service delivery algorithm. Lessons learned during the pilot led to the development of additional features during scale-up to exploit the other major advantages that mHealth offers including:Better supervision of health workers and accountability for their performanceImproved communication between supervisors and workersAccess to real-time data and reports to support quality im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…The data collected during these routine community-level service-provision visits were stored in electronic forms and sent to a central server that could be accessed by district-level health staff. 57 This type of intervention improves not only the quality and comprehensiveness of services provided by lay health workers at the community level but also facilitates appropriate linkages to care and management at the facility level.…”
Section: Resultsmentioning
confidence: 99%
“…The data collected during these routine community-level service-provision visits were stored in electronic forms and sent to a central server that could be accessed by district-level health staff. 57 This type of intervention improves not only the quality and comprehensiveness of services provided by lay health workers at the community level but also facilitates appropriate linkages to care and management at the facility level.…”
Section: Resultsmentioning
confidence: 99%
“…This can be in the form of checklists for routine care such as antenatal visits, decision support for diagnosis of illness, and video or graphic counseling messages from the provider directly to the client. Numerous studies have shown the advantage of using decision support, 10,11 video counseling, 12 and digital supervision strategies 13 to improve quality. Though many of these strategies are in their infancy, they are increasingly being adopted by countries as core components of their health strategies.…”
Section: Health Workers Will Be Digitally Supportedmentioning
confidence: 99%
“…We adapted the BCS, a toolkit developed by the Population Council to facilitate high-quality, individualised contraceptive counselling. [22][23][24] The BCS uses a series of questions to narrow method choices to those that are most consistent with a woman's reproductive values and preferences. Visual aids are used to guide counselling and illustrate the relative effectiveness of the methods.…”
Section: Interventionmentioning
confidence: 99%